ESL Teachers’ Perceptions on Shifting from a Deductive to an Inductive Approach: Enhancing Communicative Competence in Sri Lankan Classrooms. - Kumara, P.G.S.R. (University of Jaffna, 2025)
In recent years, the global focus in second language instruction has shifted from grammar-based accuracy to real-world communication skills. This transition is especially relevant in Sri Lankan ESL classrooms where traditional methods continue to dominate. The predominant pedagogical approach in Sri Lankan English as a Second Language (ESL) - classrooms is deductive learning, where teachers explicitly introduce grammar rules before guiding students through controlled exercises. While this method fosters grammatical accuracy, it often fails to enhance communicative competence and real-world language application. As a result, students excel in written examinations but struggle with practical English usage due to limited engagement in spontaneous communication. This challenge is further exacerbated by minimal student interaction and rigid instructional practices, reinforcing English as an academic subject rather than a functional tool for communication. Consequently, Sri Lankan ESL learners often demonstrate passive language skills in communicative settings, limiting their ability to engage in real-world English conversations. An alternative approach, inductive learning, shifts the focus towards student-centered discovery, allowing learners to infer grammatical principles through contextual examples, interaction, and problem-solving. This method has been recognized globally for improving critical thinking, learner autonomy, and communicative skills. Unlike the traditional rule-based approach, inductive learning creates an immersive learning environment, where students actively participate in the learning process by exploring examples and identifying patterns. However, its implementation in Sri Lanka remains limited due to institutional constraints, teacher preparedness, and resource availability. Many Sri Lankan teachers are accustomed to exam oriented teaching, making it difficult to transition into a more communicative framework. Moreover, existing research primarily focuses on grammar-based instruction and test performance, leaving a significant gap in understanding how teaching methodologies impact spoken fluency, practical application, and ESL learner motivation. This study explores ESL teachers’ perceptions of transitioning from deductive to inductive learning and examines how this shift influences communicative competence and classroom practices. The research employs a qualitative case study approach, involving 25 ESL teachers from various secondary schools in the Monaragala Education Division. Participants were selected using purposive sampling, ensuring the representation of different teaching experiences and ESL proficiency levels. Data was collected through semi- structured interviews and classroom observations, with thematic analysis is used to identify teacher attitudes, challenges, and instructional effectiveness patterns. Additionally, classroom discourse analysis and task-based evaluations assessed students’ communicative ability and practical English usage. By integrating authentic speaking tasks, peer discussions, and scenario-based activities, the study measured how inductive learning impacts students’ spoken proficiency in comparison to the conventional approach. Preliminary findings indicate that 40% of teachers frequently adopt inductive strategies, 35% integrate both approaches based on context, and 25% remain primarily reliant on deductive instruction. Challenges highlighted include insufficient training in inductive teaching techniques, resistance to curriculum modifications, and lack of teaching resources. Many teachers expressed concerns regarding time constraints and syllabus coverage, as inductive learning often requires longer engagement periods for students to internalize concepts. However, teachers who implemented inductive strategies reported higher student engagement, improved confidence in spoken English, and greater retention of language structures. These results align with global studies that emphasize learning by doing as an essential method for fostering long-term language thematacquisition. The study underscores the need for curriculum reforms that balance both deductive and inductive methodologies to create a more interactive and communicative learning environment. Based on these findings, teacher training programs should incorporate inductive methodologies, equipping educators with practical strategies for fostering real-world language application. Moreover, professional development workshops should be introduced to help teachers adapt to modern pedagogical approaches that prioritize communicative competence. Additionally, schools should integrate technology-driven learning tools, such as digital storytelling, role-play simulations, and interactive language applications, to enhance engagement and language acquisition. The implementation of blended learning models, where digital tools supplement face-to-face instruction, can further bridge the gap between traditional methods and communicative learning. By addressing institutional barriers and promoting interactive teaching techniques, this research provides actionable recommendations for curriculum developers, policymakers, and ESL educators, contributing to more effective language instruction in Sri Lanka. It highlights the importance of aligning ESL instruction with real-world demands, ensuring that students not only excel academically but also develop the ability to communicate effectively in diverse social and professional environments. Future research should explore longitudinal studies on how inductive learning impacts language retention and long-term communicative success among Sri Lankan ESL learners.
Keywords: ESL teaching; Deductive learning; Inductive learning; Learner autonomy; Blended learning; Teacher training; Communicative competence